Workplace-based interventions to promote healthy lifestyles in the NHS workforce: a rapid scoping and evidence map - Gary Raine; Sian Thomas; Mark Rodgers; Kath Wright; Alison Eastwood (National Institute for Health Research, 2020)
Background: The health and well-being of staff working in the NHS is a significant issue for UK health care. We sought to identify research relevant to the promotion of healthy lifestyles among NHS staff on behalf of NHS England. Objectives: To map existing reviews on workplace-based interventions to promote health and well-being, and to assess the scope for further evidence synthesis work. Design: Rapid and responsive scoping search and evidence map. Participants: Adult employees in any occupational setting and in any role. Interventions: Any intervention aimed at promoting or maintaining physical or mental health and well-being. Early intervention initiatives and those addressing violence against staff, workplace bullying or harassment were also included. Main outcome measures: Any outcome related to the effectiveness, cost-effectiveness or implementation of interventions. Data sources: A scoping search of nine databases was conducted to identify systematic reviews on health and well-being at work. Searches were limited by publication date (2000 to January/February 2019). Review methods: The titles and abstracts of over 8241 records were screened and a total of 408 potentially relevant publications were identified. Information on key characteristics were extracted from the titles and abstracts of all potentially relevant publications. Descriptive statistics (counts and percentages) for key characteristics were generated and data from reviews and 'reviews of reviews' were used to produce the evidence map. Results: Evidence related to a broad range of physical and mental health issues was identified across 12 'reviews of reviews' and 312 other reviews, including 16 Cochrane reviews. There also exists National Institute for Health and Care Excellence guidance addressing multiple issues of potential relevance. A large number of reviews focused on mental health, changing lifestyle behaviour, such as physical activity, or on general workplace health/health promotion. Most of the reviews that focused only on health-care staff addressed mental health issues, and stress/burnout in particular. Limitations: The scoping search process was extensive and clearly effective at identifying relevant publications, but the strategy used may not have identified every potentially relevant review. Owing to the large number of potentially relevant reviews identified from the scoping search, it was necessary to produce the evidence map using information from the titles and abstracts of reviews only. Conclusions: It is doubtful that further evidence synthesis work at this stage would generate substantial new knowledge, particularly within the context of the NHS Health and Wellbeing Framework[NHS England. Workforce Health and Wellbeing Framework. 2018. URL: www.nhsemployers.org/-/media/Employers/Publications/Health-and-wellbeing/NHS-Workforce-HWB-Framework_updated-July-18.pdf (accessed 10 January 2019)] published in 2018. Additional synthesis work may be useful if it addressed an identifiable need and it was possible to identify one of the following: (1) a specific and focused research question arising from the current evidence map; it may then be appropriate to focus on a smaller number of reviews only, and provide a more thorough and critical assessment of the available evidence; and (2) a specific gap in the literature (i.e. an issue not already addressed by existing reviews or guidance); it may then be possible to undertake further literature searching and conduct a new evidence review. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 18. See the NIHR Journals Library website for further project information.